PantanalQuest: Integrando o Ensino de Biomas e o Pensamento Computacional. - BEATRIZ LIMA PEREIRA (2025)
The recent inclusion of Computing in Brazil's national curriculum (BNCC) has created a demand for pedagogical resources that integrate Computational Thinking (CT) with other subjects. However, developing effective educational games for this purpose remains a significant challenge. This paper addresses this challenge through a case study that reports and analyzes the conception, development, and validation process of the educational game Pantanal Quest. The methodology combined Software Engineering practices, such as agile development, with a Co-design approach involving public school Biology teachers as domain experts. The game's validation was conducted with 66 elementary school students, using the MEEGA+ model and direct observation. The evaluation results indicate high acceptance of the game regarding its aesthetics and perceived learning. The analysis also identified crucial points for improvement, such as the need to enhance initial tutorials, and validated the effectiveness of the co-design process in ensuring the pedagogical and scientific relevance of the content. We conclude that Pantanal Quest holds great potential as an interdisciplinary teaching tool. The main contribution of this work, however, lies in the detailed documentation of a participatory development methodology that can serve as a reference for future educational technology projects.